Evaluation оf the Protective Properties of Filtering Half-Masks by Measuring Pressure Difference - Golinko, V.I.; Cheberiachko, S.I.; Yavorska, O.O. (Science and Innovation, 2024)
Introduction. An important characteristic of respirator is the capability of its half-mask to protect the respiratory organs against the surrounding contaminated atmosphere due to a tight half-mask-face contact. Problem statement. Keeping a constant pressure difference under the mask is a low-cost and simple method of alternative diagnostics of half-mask protective properties involving special-purpose test aerosols. The method is based on the determination of the air amount entrained through the gaps while generating rarefaction within the under-mask area. However, there have been no recommendations on the use of the method for evaluating the insulating properties of lightweight filtering half-masks from under which it is impossible to evacuate air. Purpose is to represent a simplified method with measuring the rarefaction under a filtering half-mask making possible to determine its insulating properties and protection coefficient. Materials and methods. Protection coefficient of respirator can be evaluated in terms of air amount passing through the filtering material and gaps with the preset coefficient of penetration and suction. The latter is calculated as coefficient of aspiration into the gap of the preset length. Air consumption is determined experimentally as pressure difference between the half-mask mounted tightly on a dummy and the tubes of preset diameter positioned along the obturation line. Results. A calibration line of the relation between the pressure difference and the air consumption through a gap for the filtering half-masks has been developed. Coefficients of insulation and protection of Lepestok-type respirators have been calculated. The protection coefficients have been established to proportionally depend on the ratio of air consumption through a filter and gaps between the face and the half-mask along the obturation line. Conclusions. It has been proved that the methods for determining the protective properties of filtering half-masks in terms of measuring pressure difference may be used as a low-cost alternative to expensive diagnostics of the quality of respiratory protective devices. Also, they can be employed for selecting and training workers to properly use the respirators under manufacturing conditions in accordance with EN529:2006 requirements.